Bcl-2 Homodimerization Involves Two Distinct Binding Surfaces, a Topographic Arrangement That Provides an Effective Mechanism for Bcl-2 to Capture Activated Bax* - Zhang, Zhi; Lapolla, Suzanne M.; Annis, Matthew G.; Truscott, Mary; Jane Roberts, G.; Roberts, G. Jane; Miao, Yiwei; Shao, Yuanlong; Tan, Chibing; Peng, Jun; Johnson, Arthur E.; Zhang, Xuejun C.; et al. (Journal of Biological Chemistry, 2004)
The homo- and heterodimerization of Bcl-2 family proteins is important for transduction and integration of apoptotic signals and control of the permeability of mitochondria and endoplasmic reticulum membranes. Here we mapped the interface of the Bcl-2 homodimer in a cell-free system using site-specific photocross-linking. Bcl-2 homodimer-specific photoadducts were detected from 11 of 17 sites studied. When modeled into the structure of Bcl-2 core, the interface is composed of two distinct surfaces: an acceptor surface that includes the hydrophobic groove made by helices 2 and 8 and the loop connecting helices 4 and 5 and a donor surface that is made by helices 1–4 and the loop connecting helices 2 and 3. The two binding surfaces are on separate faces of the three-dimensional structure, explaining the formation of Bcl-2 homodimers, homo-oligomers, and Bcl-2/Bax hetero-oligomers. We show that in vitro the Bcl-2 dimer can still interact with activated Bax as a larger oligomer. However, formation of a Bax/Bcl-2 heterodimer is favored, since this interaction inhibits Bcl-2 homodimerization. Our data support a simple model mechanism by which Bcl-2 interacts with activated Bax during apoptosis in an effective manner to neutralize the proapoptotic activity of Bax.